AFFECTIVE BEHAVIORAL THERAPY (ABT): FUNDAMENTAL PRACTICE IN THERAPEUTIC LISTENING AND OCCUPATIONAL THERAPY FOR PRIMARY CARE WORKERS DURING THE COVID-19 PANDEMIC - Márcio Fernando Da Silva; Hermano Tavares; Ciro Blujus Dos Santos Rohde (MNJ (Malang Neurology Journal), 2022)
Background: COVID-19 pandemics have triggered mental health problems in various communities. Primary healthcare workers (PHCW), are at the frontline of COVID-19 crisis, having to deal with infected patients and their families. Objective: To evaluate the efficacy of Affective Behavioral Therapy (ABT) for the treatment and prevention of mental health disorders for PHCW.  Methods: PHCW from a primary care unit (PCU) were invited to participate in an ABT group. They answered the Patient Health Questionnaire-4 (PHQ-4) about how they felt before the sessions and after them. Results: 10 sessions were offered between April and June 2020 and 30 PHCW participated, 22 women and 08 men mean age was 36.8 (SD=9.7) years old. The average number of participants per session was 4.4 (SD=2.2). Pre- and post-intervention PHQ-4 scores showed significant improvement in total score (p < 0.001). Conclusion: PHCWs mental health is strategic for the management of the community during crises related to natural crises. The ABT was effective in supporting the mental health of PHCW during the COVID-19 epidemic. Future controlled studies must be conducted in order to further test its efficacy.  Keywords: COVID-19, mental health, primary care, therapeutic listening, occupational therapy, affective behavioral therapy